Restoration ecology - Greipsson, Sigurdur; Greipsson, Sigurdur (Sudbury, Jones and bartlett, 2011)
The discipline of restoration ecology aims to provide a scientifically sound basis for the reconstruction of degraded or destroyed ecosystems to produce self-supporting systems. This new text provides a current, comprehensive look at this developing area of study that is ideal for the upper-level undergraduate or graduate level course. Divided into five natural parts, Restoration Ecology opens with a look at ecological perspectives of restoration, including nutrient cycling and factors that regulate ecosystem function. The text then moves on to discuss the ecological theories that have shaped restoration ecology, and moves on to sections devoted to restoration in practice, providing accounts of real restoration of various ecosystems. The final section delves in to the planning, implementation, monitoring and appraisal of restoration work.
Index 387-408p.
Keywords: Biology; Restoration ecology; Botany